Full Stack JavaScript Learn Backbone.js, Node.js and MongoDB - Mardan, Azat. (Apress : Imprint: Apress, 2015)
This is a hands-on book which introduces you to agile JavaScript web and mobile software development using the latest cutting-edge front-end and back-end technologies including: Node.js, MongoDB, Backbone.js, Parse.com, Heroku and Windows Azure. Practical examples include building multiple versions of the Chat app: •jQuery + Parse.com JS REST API •Backbone and Parse.com JS SDK •Backbone and Node.js •Backbone and Node.js + MongoDB The Chat application has all the foundation of a typical web/mobile application: fetching data, displaying it, submitting new data. Other examples in the book are as follows: •jQuery + Twitter RESP API “Tweet Analyzer” •Parse.com “Save John” •MongoDB “Print Collections” •Backbone.js “Apple Database” •Monk + Express.js “REST API Server” This book will save you many hours by providing a hand-picked and tested collection of quick start guides. RPJS has practical examples that allow to spend less time learning and more time building your own applications. Prototype fast and ship code that matters! What You will Learn: You should expect a basic understanding from a collection of quick start guides, tutorials and suggestions for the devel0pment apps discussed in this book. In addition to coding examples, the book covers virtually all setup and deployment step-by-step. You’ll learn from the examples of Chat web/mobile applications starting with front-end components and by the end we’ll put front-end and back-end together and deploy to the production environment. Who This Book is For: The typical programmer who wants to learn more about effective JavaScript coding.